Sea Surface Monitoring System as a Support for Rob Mitigation Using Wemos D1 Microcontroller Based on Internet of Things - Ariwirawan Djali; Iskandar Fitri; Sari Ningsih (Institute of Computer Science (IOCS), 2020)
Rob is a flood disaster that is generally caused by the flow of strong water that rises to lower land. In other cases, the occurrence of tides is due to the meeting of tides with the flow of the river so that the overflow of water into the mainland. Therefore, to support the mitigation of tidal disasters, researchers took the initiative to design a water level monitoring tool to provide early warning information about tidal disasters in real-time. The design of the tool uses an ultrasonic sensor and a Wemos D1 R1 microcontroller as a prototype of seawater level detection devices, then sensor data will be sent to thingspeak to be monitored in real-time so as to produce output in the form of warning notifications via telegram on smartphones and social media information on Twitter and Facebook. The results of testing the system and tools are able to work as expected. When the sensor reads the water level between 26 <35cm it will be alerted to a telegram alert with a delivery time of 17 seconds, and the system will automatically post warning information via Facebook with a duration of 10 seconds and Twitter for 13 seconds. However, if the water level is <25cm, the hazard notification will appear continuously every 16 seconds by telegram. The results of testing the sensor data accuracy there is a difference of an average error value of 3.68cm with an error percentage of 7.7%.